Neurobehavioral Alterations in Occupational Noise Exposure: A Systematic Review - Nicola Mucci (MDPI AG, 2021)
The psychology of sustainability and sustainable development emphasizes the value to ensure health and well-being in different environments, including workplaces. Chronic exposure to noise can cause several extraordinary effects and involve all the systems of the human organism. In addition to cardiovascular, gastrointestinal, and immune effects, the data in the literature show alterations in behavioral disturbances, memory capacity, and cognitive performance. Through this systematic review, the authors try to find out the main neurobehavioral alterations in the case of occupational exposure to noise. The literature review included articles published in the major databases (PubMed, Cochrane Library, Scopus, Embase), using a combination of some relevant keywords. This online search yielded 4434 references; after selection, the authors analyzed 41 articles (4 narrative reviews and 37 original articles). From this analysis, it appears that the main symptoms are related to psychological distress, annoyance, sleep disturbances, and cognitive performance. Regarding tasks, the most frequent employments concern school staff, followed by employees from various industrial sectors and office workers. Although the causes are still widely debated, it is essential to protect these workers against chronic exposure to noise. In fact, in addition to a hearing loss, they can manifest many other related discomforts over time and compromise their full working capacity, as well as expose them to a greater risk of accidents or absences from work.